Role of C-Reactive Protein, Erythrocyte Sedimentation Rate, Progesterone and Estradiol Hormone Levels in First Trimester Threatened Abortion: Peran C-Reactive Protein, Laju Endap Darah, Progesteron dan Estradiol pada Abortus Imminens Trimester Pertama - Rajuddin Rajuddin; Fitra Rizia; Sarah I. Nainggolan (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: To assess correlation of High sensitivity C-Reactive Protein (Hs-CRP), erythrocyte sedimentation rate (ESR), progesterone and estradiol levels in the first trimester threatened abortion incidence in Dr. Zainoel Abidin Hospital, Banda Aceh.Methods: Case control design used in this study divided threatened abortion into a case group and normal pregnancy into a control group with a total of 20 subjects for each group. This research was conducted in the Emergency Room and Obstetric Ward of Dr. Zainoel Abidin hospital Banda Aceh in 2019. Eta correlation test was conducted to find out the link between variables towards threatened abortion with 95% confidence level followed by the Receiver Operating Curve (ROC) analysis to find out the cut off points.Results: Progesterone levels (14.76 ng/mL), estradiol (427.61 pg/mL), Hs-CRP (2.57 mg/L) and ESR (28.75 mm/hour) case group were lower compared to the control group. Incidence of threatened abortion correlates to progesterone and estradiol with the correlation strength respectively -0.838 and -0.416.Conclusion: Progesterone and estradiol correlate negatively with first-trimester abortion incidence. Evaluation of these two hormones levels is useful for diagnostic purposes and screening of threatened abortion with a cut point of progesterone 23.03 ng/mL and estradiol 468.8 pg/mL.Keywords: C-Reactive Protein, erythrocyte sedimentation rate, estradiol, progesterone, threatened abortion Abstrak Tujuan: Penelitian ini bertujuan untuk menilai korelasi antara kadar High sensitivity C-Reactive Protein (Hs-CRP), Laju Endap Darah (LED), progesteron dan estradiol terhadap kejadian abortus imminens pada trimester pertama di RSUD Dr. Zainoel Abidin Banda Aceh. Metode: Desain kasus kontrol digunakan dalam penelitian ini dimana kejadian abortus imminens menjadi kelompok kasus dan kehamilan normal menjadi kelompok kontrol dengan jumlah masing-masing kelompok sebanyak 20 sampel. Penelitian ini dilakukan di Instalasi Gawat Darurat dan ruang rawat Obstetri Rumah Sakit Umum Dr. Zainoel Abidin (RSUDZA) Banda Aceh pada tahun 2019. Uji korelasi Eta digunakan untuk mengetahui korelasi antar variabel terhadap abortus imminens dengan tingkat kepercayaan 95% dilanjutkan dengan analisis Receive Operating Curve (ROC) untuk menentukan titik potong. Hasil: Kadar progesteron (14,76 ng/mL), estradiol (427,61 pg/mL), Hs-CRP (2,57 mg/L) dan LED (28,75 mm/jam) kelompok kasus lebih rendah dibandingkan kelompok kontrol. Kejadian abortus imminens berkorelasi terhadap progesteron dan estradiol dengan kekuatan korelasi (R) secara berurutan -0,838 dan -0,416. Kesimpulan: Progesteron dan estradiol berkorelasi negatif terhadap kejadian abortus imminens pada trimester pertama kehamilan. Evaluasi kadar kedua hormon tersebut bermanfaat untuk kepentingan diagnostik dan penapisan abortus imminens dengan titik potong progesteron 23,03 ng/mL dan estradiol 468,8 pg/mL. Kata kunci: abortus imminent, C-Reactive Protein, estradiol, laju endap darah, progesteron